2018
DOI: 10.1080/17435390.2018.1464229
|View full text |Cite
|
Sign up to set email alerts
|

Multi-level toxicity assessment of engineered cellulose nanofibrils inDaphnia magna

Abstract: Cellulose nanofibril (CNF)-based materials are increasingly used in industrial and commercial applications. However, the impacts of CNF on aquatic life are poorly understood, and there are concerns regarding their potential toxicity. Using a combination of standard ecotoxicological tests and feeding experiments, we assessed the effects of CNF exposure (0.206-20.6 mg/L) on the feeding (food uptake and gut residence time) and life-history traits (growth and reproduction) in the cladoceran Daphnia magna. No morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…20 Contrariwise, Daphnia magna treated with CSC nanofibrils (0.206–20.6 mg L −1 ) showed no clinical signs of toxicity (no mortality, no apparent translocation of CSC nanofibrils across the alimentary canal, and no aberrant behavior) after 21 days of treatment. 21 Also, another study showed low toxicity potential of surface-modified CSC-nanocrystals and CSC-nanofibers in embryonic zebra fish. 22 We had also previously reported that oral administration of sulfonated CSN could cause mild toxicity in rat renal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…20 Contrariwise, Daphnia magna treated with CSC nanofibrils (0.206–20.6 mg L −1 ) showed no clinical signs of toxicity (no mortality, no apparent translocation of CSC nanofibrils across the alimentary canal, and no aberrant behavior) after 21 days of treatment. 21 Also, another study showed low toxicity potential of surface-modified CSC-nanocrystals and CSC-nanofibers in embryonic zebra fish. 22 We had also previously reported that oral administration of sulfonated CSN could cause mild toxicity in rat renal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…3A. Ogonowski et al (2018) have examined the response of D. magna neonates after 48 h of exposure to CNFs and also observed no mortality.…”
Section: Nanocelluloses Induced Toxicity and Oxidative Stress Responsmentioning
confidence: 99%
“…Vartiainen et al (2011) detected acute toxicity of microfibrillated cellulose referred to as nanocellulose only at a very high level (300 mg/L) to Vibrio fischeri, and detected decrease in Daphnia magna movement induced by the microfibrillated cellulose. Ogonowski et al (2018) also concluded that CNFs display a low toxic potential to filter-feeding organism (D. magna). In addition, Salehpour et al (2018) found that the nanocomposites of polyvinyl alcohol and CNFs did not generate any negative effects on plants including cress and spinach.…”
Section: Introductionmentioning
confidence: 99%
“…CNF further caused peritoneal inflammation [19]. In Daphnia magna CNF displayed a low-toxic potential, indicating a low environmental risk factor [22]. The current study used the Drosophila model to check the toxicity of CNF.…”
Section: Introductionmentioning
confidence: 99%